Sistem Prediksi Kondisi Kesehatan Pasien Penderita Talasemia dengan Menggunakan Logika Fuzzy Tsukamoto - Cintya Fransisca Wijaya; Lena Magdalena; Reza Ilyasa (Maranatha University Press, 2021)
Thalassemia is a hereditary disease that makes sufferers experience red blood cell abnormalities and must receive continuous blood transfusions throughout their lives. Gunung Jati Hospital, Cirebon City handles registration and scheduling of thalassemia patients with assistance from Perhimpunan Orang tua Penderita Talasemia Indonesia (POPTI). In handling patient data, it is necessary to have a system that facilitates all activities ranging from registration, scheduling, and make predictions about the patient's health condition along with recommendations for handling the patient's condition. The purpose of this study is to make a prediction system for health conditions related to thalassemia suffered by patients based on influencing variables using the Fuzzy Tsukamoto method. This system can also handle patient data, scheduling, and storing patient medical recap data. The final results of this system are patient data, patient care schedules, predictions of patient health conditions, and recommendations for patients. Keywords— Fuzzy; Prediction; thalassemia; Tsukamoto.